Gender differences in life satisfaction and social participation - Stephan Humpert (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This paper deals with the effects of social participation activities on life satisfaction. Using the German General Social Survey (ALLBUS) for 2010, I present gender specific differences for several social activities, such as club memberships of political, welfare, health or more leisure time orientated groups. These activities have different impacts on male or female satisfaction. While sports and civic engagements improve only female life satisfaction, men are more affected by charity organizations or leisure time activities, such as hobbies. It is an interesting result that political activities and trade unions have no, or even negative effects on life satisfaction.
Keywords: D60; I31; O52; Z13; 330; subjective well-being; social participation; German General Social Survey (ALLBUS)